Beacon of Hope Fades: Russia’s Withdrawal from BSGI in 2023 - Imam Syafi'ie; Intan Annisa Putri; Nur Rachmat Yuliantoro (Jurnal Hubungan Internasional, 2026)
The Russia-Ukraine war has caused global instability in various fields. One of them is food supply instability, which could threaten global food security. To address this threat, the United Nations and Türkiye mediated the Black Sea Grain Initiative (BSGI), a humanitarian initiative to ensure the safety of export traffic in the Black Sea. Over the course of a year, the BSGI has been considered successful in alleviating food shortages and reducing grain prices by up to 23%. However, the BSGI had to be suspended because Russia, as a party, withdrew. This study analyzes whether Russia’s actions constitute the weaponization of food and, if so, how. Guided by the definition of “food as weapon” and the concept of weaponization of food, this study argues that by withdrawing from the BSGI, Russia has weaponized food using two methods, namely: attacks on agricultural infrastructure and supply chains, and the use of food to gain support from African countries by providing them free grain and foodstuffs. It will also explain how the end of the BSGI has negatively impacted global food security and contributed to the continuation of the Russia-Ukraine conflict. Keywords: Russia-Ukraine conflict, Black Sea Grain Initiative, food security, weaponization of food, International Relations.